Comparative of Leadership in Public Service: In-Group and Out-Group - Saleh, Reza; Saleh, Dean Subhan (Fakultas Ekonomi dan Bisnis Universitas Islam DR KH EZ Mutaqien, 2024)
Effective leadership requires a close relationship between leader (L) and follower (F), with L-F exchange occurring both internally and externally in the organization. This study compares ef-fective leadership in in-group and out-group L-F dyads in a public organization, namely the Tax Service Offices. This study applied a quantitative research method and Structural Equation Mod-eling (SEM) to 774 respondents who have leader-follower dyadic relationships. The results show that: (i) there are differences in leader and follower perceptions regarding turbulence, adaptive behavior, responsive behavior, and transactional leadership in directly influencing performance; (ii) adaptive behavior mediates performance in in-group relationships, whereas responsive be-havior mediates performance in out-group relationships; and (iii) transactional leadership has a direct influence on performance in in-group relationships, while in out-group relationships, there is no direct influence on performance.